Analysis of productivity of apiculture among ADP contact farmers in Ohafia agricultural zone of Abia State, Nigeria - Ebe, F. E.; Obike, K. C; Oti, O. G.; Agha, U. J. (ADAN JOURNAL OF AGRICULTURE, 2024)
This study was conducted in Ohafia Agricultural Zone of Abia State. The study assessed the productivity of ADP contact apiculturists and the constraints militating against the productivity of the apiculturists. The study used purposive and random sampling techniques to select 60 beekeepers. Data were collected from the apiculturists through primary source. The collected data were analysed using total factor productivity, multiple regression analysis and Likerty scale. The result of the findings showed that mean productivity of the apiculturists was 4.25kg/N. The result further indicated that education, experience and number of bee hive positively and significantly influenced the productivity of the respondents while age was negatively signed and significant. The major constraints on the productivity were climate change, bush burning, deforestation, poor government intervention, poor extension contact etc. Policy should aim at full implementation of laws guiding bush burning and deforestation. The farmers should be advised to always clear the bushes around their beekeeping surroundings at the onset of dry seasons in order to ward off the bush being burned by fire. Also the few extension agents in the field should be encouraged to visit and teach the apiculturists the improved technologies on beekeeping so as to increase the knowledge of the beekeepers and enhance the productivity of the apiculturists.